2003
DOI: 10.1046/j.1440-1827.2003.01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma with osteoclast‐like giant cells: Possibility of osteoclastogenesis by hepatocyte‐derived cells

Abstract: Giant cell tumor (GCT) of bone is a primary osteolytic tumor that is characterized by the formation of osteoclast-like giant cells. In addition to GCT of bone, extraskeletal GCT are known to be formed in several soft tissues. Giant cells in GCT of bone were suggested to be identical to osteoclasts, but the characterization of giant cells in extraskeletal GCT remains incomplete. In this study, a case of sarcomatoid hepatocellular carcinoma with osteoclast-like giant cells was analyzed. Immunohistochemistry reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 26 publications
2
48
0
1
Order By: Relevance
“…Sir: Tumours with an osteoclast‐like giant cell (OGC) component have been described in a wide variety of organs outside bone: most of them are now considered to be undifferentiated carcinomas with the potential for intratumoral osteoclastogenesis. Hepatic neoplasms with OGCs are quite uncommon 1 . Here, we report a case of undifferentiated carcinoma of the liver with an abundant component of OGC.…”
Section: Review Of Hepatic Tumours With Osteoclast‐like Giant Cells Pmentioning
confidence: 91%
See 1 more Smart Citation
“…Sir: Tumours with an osteoclast‐like giant cell (OGC) component have been described in a wide variety of organs outside bone: most of them are now considered to be undifferentiated carcinomas with the potential for intratumoral osteoclastogenesis. Hepatic neoplasms with OGCs are quite uncommon 1 . Here, we report a case of undifferentiated carcinoma of the liver with an abundant component of OGC.…”
Section: Review Of Hepatic Tumours With Osteoclast‐like Giant Cells Pmentioning
confidence: 91%
“…Only 10 cases of ‘primitive osteoclast‐like giant cell tumours’ have been described in the liver, most of them considered to be primitive undifferentiated carcinomas; despite the lack of epithelial differentiation, most of them have displayed phenotypic evidence of an epithelial lineage (Table 1). 1,3–11 …”
Section: Review Of Hepatic Tumours With Osteoclast‐like Giant Cells Pmentioning
confidence: 99%
“…[1][2][3][4][5][6] These giant cells cut sections of the resected specimen showed that the tumor was widely extended through the gallbladder wall (6 cm maximum width), and had directly invaded the liver parenchyma (Fig. 3b).…”
Section: Introductionmentioning
confidence: 99%
“…Osteoclasts may also be seen in carcinomas of visceral organs, gastrointestinal stromal tumors and leiomyosarcomas [22-24]. These tumors should be clearly differentiated from tumors with typical morphological features of GCT accompanying to an in situ or invasive carcinoma to prevent an overdiagnosis of 'undifferentiated carcinoma'.…”
Section: Discussionmentioning
confidence: 99%